Attitudes of Lithuanian Americans Regarding Persecution of War Criminals During the Cold War: The Issue of Relations With Jews - Stončius, Justas (History / Istorija, 2024)
Abstract. In the early 1970s, as the topic of war criminals became increasingly popular in the United States, concerns arose about many of them living freely. Among the suspects of war crimes were Lithuanian expatriates. The article analyses the prevailing attitudes of Lithuanian-Americans (primarily of main organisations) towards the prosecution of war criminals during the Cold War, and how this affected relations/communication with Jewish organisations (in the US and Israel). The research revealed that the prosecution of suspects, especially with the establishment of the Office of Special Investigations (OSI) within the Department of Justice in 1979, negatively affected the relationship between Lithuanian-Americans and Jews, and highlighted conflicts caused by a lack of empathy for the differing experiences of the Soviet and Nazi occupations of Lithuania.